Cholesterol from Prawn-Head Waste - Neelakanta Kaimal, M N; Rao, V Seshagiri (Fishery Technology, 1965)
A process is described for the isolation of Cholesterol from the fat obtained from prawn head-waste. Cholesterol of about 94: percent purity is obtained. The final yield on the basis of fat is about 2 per cent.